THE ROLE OF GASTRONOMIC TOUR GUIDES IN ENHANCING CULINARY IDENTITY IN THE CITY OF BANDUNG - Debi Rusmiati (Politeknik Pariwisata Palembang, 2025)
Food is not only about taste, but also about identity which represents the social and cultural life of a society that reflects a long story in every ingredient, cooking method and serving method. Bandung City offers a variety of culinary delights, both traditional and the result of cultural acculturation that are not only delicious, but also full of philosophy. Looking back, Bandung City Culinary is influenced by several cultural acculturations, namely Chinese, indigenous and the result of acculturation from the Dutch who used to live in Bandung City. Culinary for Bandung City is an important part of tourism activities because it has its own appeal. This study aims to explore the role of gastronomic tour guides in enhancing culinary identity in Bandung City and to analyze tour guides in delivering culinary tours to tourists. This study uses a qualitative method with an ethnographic approach where researchers are directly involved in gastronomic tour activities. The results of this study indicate that tour guides have a role in enhancing culinary identity in Bandung City. This can be seen from the choice of information delivery method when conducting guidance.